Pelestarian Beripat Beregong Untuk Mendukung Kemajuan Pariwisata Belitong - Peranciscus Aryanto; Ute Lies Siti Khadjah; Wawan Setiawan (Politeknik Pariwisata NHI Bandung, 2022)
Beripat-beregong is a martial art that combines elements of music, agility and courage. In the past, beregong beregong became a place to compete knowledge. This shows the spiritual wealth in society. A few important ones. First, the rhythm of the sound of the gongs leads to the beauty of the movements of the fighters as well as in life how hard a life is lived if it is lived with pleasure, full of beauty, it will be more valuable and meaningful. Second, Courage, self-confidence is the basis for competing against agility. Third, the cultivation of brotherly values. There can be no fight between brothers, there can be no revenge nor the enormity of the fight. The study used a qualitative descriptive method. Collecting data through interviews and field observations. The results of the study indicate that the beregong-shaped tourist attraction can be an attraction for tourists and has a very distinctive cultural value from Belitong Island. The research results can be used as a driving force for the development of Belitong Island tourism.